Potassium Channel Candidate Genes Predict the Development of Secondary Lymphedema Following Breast Cancer Surgery. Issue 2 (March 2017) - Smoot, Betty; Kober, Kord M.; Paul, Steven M.; Levine, Jon D.; Abrams, Gary; Mastick, Judy; Topp, Kimberly; Conley, Yvette P.; Miaskowski, Christine A.
Abstract : Background: Potassium (K + ) channels play an important role in lymph pump activity, lymph formation, lymph transport, and the functions of lymph nodes. No studies have examined the relationship between K + channel candidate genes and the development of secondary lymphedema (LE). Objective: The study purpose was to evaluate for differences in genotypic characteristics in women who did ( n = 155) or did not ( n = 387) develop upper extremity LE following breast cancer treatment based on an analysis of single-nucleotide polymorphisms (SNPs) and haplotypes in 10 K + channel genes. Methods: Upper extremity LE was diagnosed using bioimpedance resistance ratios. Logistic regression analyses were used to identify those SNPs and haplotypes that were associated with LE while controlling for relevant demographic, clinical, and genomic characteristics. Results: Patients with LE had a higher body mass index, had a higher number of lymph nodes removed, had more advanced disease, received adjuvant chemotherapy, received radiation therapy, and were less likely to have undergone a sentinel lymph node biopsy. One SNP in a voltage-gated K + channel gene ( KCNA1 rs4766311), four in two inward-rectifying K + channel genes ( KCNJ3 rs1037091 and KCNJ6 rs2211845, rs991985, rs2836019), and one in a two-pore K + channel gene ( KCNK3 rs1662988) were associated with LE. Discussion: These preliminary findings suggest that K + channel genes play a role in the development of secondary LE.